A Critical Study of Metalinguistic Corrective Feedback in the Essays by XII Students of JNV Patan - Soumita Sarkar; Bharti Girish Dave (Yayasan Visi Intan Permata, 2024)
Corrective feedback (CF) is a vital aspect in the field of English language teaching, which is complex and continually evolving. English language teachers dedicate significant time and effort to provide feedback on students' writing performance. There is an ongoing debate regarding the efficacy of the teachers’ CF to improve the learners’ English writing competency. Empirical studies on CF in the Indian context are scarce. This study looks at how direct focused metalinguistic and non-metalinguistic written corrective feedback (WCF) affects the use of noun inflections in English descriptive essays written by Class XII students of Jawahar Navodaya Vidyalaya, Patan. The study involves two experimental groups and one control group of ten students each; the first group received metalinguistic WCF; the second received non-metalinguistic WCF; and the control group received no feedback. A pretest-treatment-post-test-delayed post-test format was utilized to extract the data. The findings suggest that the teacher's targeted direct metalinguistic WCF led to inconsistent improvements in the learners' written output. However, this approach has certain limitations, including issues related to time frame, scaffolding, personalized feedback, as well as sustained teacher’s monitoring, and other factors pertaining to learners’ proficiency, personality, retention, and revision.